Pengaruh Pemberian Artemia Sp. yang Diperkaya Minyak Cumi dengan Dosis Berbeda dalam Meningkatkan Kelangsungan Hidup Larva Udang Vaname (Litopenaeus Vannamei) - Siti Amelia Gumohung; Yuniarti Koniyo; Arafik Lamadi (Research Review: Jurnal Ilmiah Multidisiplin, 2024)
This study aims to determine the effect of giving Artemia sp. enriched with squid oil at different doses to increase the survival of vannamei shrimp larvae (Litopenaeus vannamei). This study is conducted using the experimental method. The test animals used are 600 v an a m ei shrimp larvae (Litopenaeus vannamei), with treatment A (Control), B (20 individuals/head), C(25 individuals/head), and D(30 individuals/head). The containers used are 12 pieces of styrofoam with a volume of 30 L, and each contains 50 vaname shrimp larvae (Litopenaeus vannamei). This study lasted for 30 days. Furthermore, the design used ni this study is a Completely Randomized Design (CRD) using Analysis of Variance (ANOVA). Further tests are carried out using the Least Significant Difference (BNT) test. The research findings indicate that the administration of Artemia sp. enriched with squid oil at varying doses significantly impacts the survival rates of vannamei shrimp larvae. Treatment D, with a dose of 30 individuals per larvae, exhibited the highest survival rate at 62%, whereas Treatments C, B, and A had lower survival rates of 54%, 49%, and 41%, respectively. Treatment D was considered the most effective in this study. These findings offer valuable insights for the development of more effective and efficient vannamei shrimp farming practices.